Exploring physician and patient perspectives on expectations and role models towards chronic pain treatment in general practice: a qualitative cross-sectional study - Dupont, Dominik; Brinkmöller, Sabrina; Carter, Sarina; Wensing, Michel; Straßner, Cornelia; Engeser, Peter; Poß-Doering, Regina (Healthcare, 2025)
Background and Objective: Approximately 7.4% of the German population matched the criteria of impeding, chronic non-cancer-related pain in 2014. Guidelines emphasize the importance of a holistic treatment approach. The project RELIEF aims to develop and evaluate a multifaceted case-management intervention to foster the holistic management of chronic pain in general practice. To inform intervention development, this study explored expectations and perceived role models of general practitioners (GP) and patients regarding chronic non-cancer-related pain management in general practice with a focus on patient expectations of GPs and themselves, as well as GP expectations of patients and their anticipation of patient’s expectations. Methods: Data were collected via semi-structured guide-based interviews with general practitioners and patients. Pseudonymized verbatim transcripts were analyzed using an inductive-deductive approach with a structuring qualitative content analysis. The Theoretical Domains Framework served as an analytical framework to explore behavioral aspects associated with expectations and role perceptions. Results:n = 25 interviews were analyzed (GP: n = 10, patient: n = 15). Findings indicate that patients considered themselves as the main actor in the therapy process yet expected guidance and care coordination from their GP. The essential role GPs play in pain management was emphasized. Role models indicated by GPs and some patients represent a care ideal, which was also reflected in discussed expectations. GPs anticipated that patients would place high relevance on pharmacological options. Patients highlighted their preference of non-pharmacological and alternative treatment options. Conclusions: Our findings demonstrate the importance of holistic, individually tailored chronic pain management in general practice. Systematic, multifaceted case management, as planned in the RELIEF project, may contribute to high-quality primary care for affected individuals.